Caracterização físico-química da bebida fermentada kombucha - Souza, Joyce Santos de (2022)
In general, consumers do not only prioritize the sensory aspects of food, but are also concerned about the benefits and functions that a product can provide. The fermented kombucha drink is consumed in several countries. It is made from an infusion of tea leaves, usually green or black, and fermented by a symbiotic combination of bacteria and yeast to form the "tea fungus". Its consumption is increasing day by day due to the delicious taste, antioxidant properties of tea extracts and beneficial effects of fermentative bacteria on human health. From the point of view that Kombucha can be a functional food, this work aims to develop and characterize the fermented Kombucha based on green tea (Camellia sinensis), evaluating the physicochemical quality under ambient conditions of temperature and pressure. Analyzes were made of green tea and kombucha at time zero, in the first 7-day aerobic fermentation. The physicochemical analyzes were pH, total acidity, Brix, reducing sugars, total phenolic compounds and flavonoids. The average acidity value of kombucha with 7 days of aerobic fermentation of 1.06g/L in acetic acid corroborated the levels indicated in the literature and a pleasant-tasting drink. The pH decreased from 4.3 to 3.3 and the acidity increased from 0.61 to 1.06 g/L in relation to the beginning of fermentation. The degree Brix decreased from 4.0 to 3.6, indicating a lower concentration of soluble solids in the final kombucha liquid. It was found that the content of reducing sugars increased after 7 days of fermentation, which is consistent with the literature. The concentration of antioxidant compounds remained practically constant at the end of the 7-day fermentation process, indicating that it is a drink rich in these compounds. In view of the studies, it is recommended to monitor the fermentation process for several days, over 7 days, and under different experimental conditions, in order to establish production standards to obtain a final product with the desirable sensory and nutritional characteristics.